Wettability alteration by new acid-alkali-surfactant-polymer formulation in high salinity carbonate reservoirs - Shuaib A, K. (Offshore Technology Conference, 2014)
Formation wettability is considered as one of the controlling parameters for residual oil recovery from carbonate reservoirs. It has a significant impact on reservoir rock properties - relative permeability and capillary pressures and consequently on oil displacement in porous media. In this paper, wettability study was conducted using natural imbibition method in the presence of acrylic acid, sodium metaborate, alpha olefin sulfonate and a copolymer. Acrylic acid was used as a precipitation inhibitor to sequester divalent cations from precipitating. The effect of different acrylic acid concentrations on interfacial tension reduction, polymer viscosity and wettability was evaluated using hard brine with a total salinity of 59,940 ppm. Various fluid-fluid interaction tests were first performed to find an optimum ratio of acrylic acid-alkali to prevent precipitations for 30 days at 80 Â°C. Based on the fluid-fluid and rock-fluids interfaces, it was observed that the combination of acrylic acid with ASP revealed positive impacts on the interfacial tension, solution viscosity and wettability alteration. Further, a considerable amount of oil was recovered during natural imbibition process. This implies strength of new Acid-Alkali-Surfactant-Polymer (AASP) formulation to alter formation wettability. Hence, AASP system can be a feasible and an alternative approach to conventional Alkali-Surfactant-Polymer (ASP) flooding technique particularly for offshore applications in which hard brine or sea water might be used to prepare ASP slug. Copyright 2014, Offshore Technology Conference.